2017
DOI: 10.4103/jispcd.jispcd_30_17
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge, attitude, and practices among dental and medical students in Eastern India – a comparative study

Abstract: Objectives:To compare oral health knowledge, attitude, and practices among dental and medical students in a Health care centre at Bhubaneswar, Odisha, India.Materials and Methods:One hundred and fifty BDS and MBBS students each from Kalinga Institute of Dental Sciences and Kalinga Institute of Medical Sciences of KIIT University, Bhubaneswar respectively, were invited to participate in this survey using a self-administered structured questionnaire in English comprising 27 questions, which was designed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…Another research shows that about 58.9% of pharmacy students had not consulted the dentist before [11] and 92.6% of students knew that the purpose of brushing teeth was to prevent tooth decay and gum disease [12]. A significant number of participants believed that the regular visit to a dentist was necessary (89.3%), when only 54% of medical students had the same opinion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Another research shows that about 58.9% of pharmacy students had not consulted the dentist before [11] and 92.6% of students knew that the purpose of brushing teeth was to prevent tooth decay and gum disease [12]. A significant number of participants believed that the regular visit to a dentist was necessary (89.3%), when only 54% of medical students had the same opinion [12].…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that women are more conscious of their appearance and body image than men and, consequently, have a proactive approach to promote and maintain oral health [ 10 ]. According to a study done in eastern India, it was concluded that female participants had a higher score in terms of knowledge and practices of oral health as compared to their male counterparts [ 11 ]. According to a study done in Jordan, it was concluded that female students brushed their teeth more frequently than male students (p<0.01) did.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the psychological reason as females show higher concern toward self-care attitudes, appearance, and self-esteem compared to the male students. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%